Cu-Catalyzed Hydrodehalogenation of Brominated Aromatic Pollutants in Aqueous Solution - Weidlich, Tomáš; Kamenická, Barbora; Beneš, Ludvík; Čičmancová, Veronika; Komersová, Alena; Cermak, Jiri; Švec, Petr (MDPI, 2021)
The catalytic effect of copper in Devarda's Al-Cu-Zn alloy (Dev. alloy) and sole metallic copper, copper salts and copper oxides in the coaction of NaBH4 within the hydrodehalogenation (HDH) of polybrominated phenols, such as the herbicide Bromoxynil in alkaline aqueous solution has been investigated. Namely, the hydrodebromination (HDB) activity of Dev. alloy/NaOH system has been compared to heterogeneous Cu-based catalysts using NaBH4 as a reductant. Differences in the solid-state structures of used Cu-based heterogeneous catalysts after the mentioned HDB process have been studied using the powder XRD and SEM techniques. It was found that some of the used copper-based catalysts are reusable and reasonably effective even at room temperature. Efficiency of the most promising copper-based reduction systems (Dev. alloy/NaOH and Cu-based catalysts/NaBH4) have been successfully tested within the HDB of industrially important brominated flame retardant tetrabromobisphenol A (TBBPA). Dev. alloy/NaOH and Cu-based catalyst generated in-situ within the CuSO4/NaBH4 produced were recognized as the most active HDB agents for complete debromination of both BRX and TBBPA.
Cu-katalyzovaná hydrodehalogenace bromovaných aromatických polutantů ve vodném roztoku
Keywords: hydrodebromination; bromophenol; copper; Devarda's Al-Cu-Zn alloy; cuprous oxide; cupric oxide; NaBH4; dehalogenation; Bromoxynil; TBBPA; hydrodebromace; bromfenol; měď, Devardova slitina; oxid měďný; oxid měďnatý, NaBH4; dehalogenace; Bromoxynil; TBBPA